Droplet Precise Self‐Splitting on Patterned Adhesive Surfaces for Simultaneous Multidetection. Issue 26 (11th May 2020) - Li, Huizeng; Fang, Wei; Zhao, Zhipeng; Li, An; Li, Zheng; Li, Mingzhu; Li, Qunyang; Feng, Xiqiao; Song, Yanlin
Abstract: Precise separation and localization of microdroplets are fundamental for various fields, such as high‐throughput screening, combinatorial chemistry, and the recognition of complex analytes. We have developed a droplet self‐splitting strategy to divide an impacting droplet into predictable microdroplets and deposit them at preset spots for simultaneous multidetection. No matter exchange was observed between these microdroplets, so they could be manipulated independently. Droplet self‐splitting was attributed to anisotropic liquid recoiling on the patterned adhesive surface, as influenced by the droplet Weber number and the width of the low‐adhesive stripe. A quantitative criterion was also developed to judge the droplet self‐splitting capability. The precise separation and distribution of microdroplets enabled simultaneous arrayed reactions and multiple analyte detection using one droplet of sample. Abstract : Dropping into place : A droplet self‐splitting strategy was developed to divide a droplet into microdroplets and deposit them in a well‐defined array. Matter exchange between the generated microdroplets was fully prohibited in the self‐splitting process, thus enabling simultaneous arrayed reactions (see picture) and the detection of multiple analytes using only one droplet of sample.